Biofilm Development by Mycobacterium avium Complex Clinical Isolates: Effect of Clarithromycin in Ultrastructure - Arij Akir; Abrar Senhaji-Kacha; Maria Carmen Muñoz-Egea; Jaime Esteban; John Jairo Aguilera-Correa (MDPI AG, 2024)
Background: The Mycobacterium avium complex includes the commonest non-tuberculous mycobacteria associated with human infections. These infections have been associated with the production of biofilms in many cases, but there are only a few studies about biofilms produced by the species included in this group. Methods: Three collection strains (M. avium ATCC25291, M. intracellulare ATCC13950, and M. chimaera DSM756), three clinically significant strains (647, 657, and 655), and three clinically non-significant ones (717, 505, and 575) of each species were included. The clinical significance of the clinical isolates was established according to the internationally accepted criteria. The biofilm ultrastructure was studied by Confocal-Laser Scanning Microscopy by using BacLight Live-Dead and Nile Red stains. The viability, covered surface, height, and relative autofluorescence were measured in several images/strain. The effect of clarithromycin was studied by using the technique described by Muñoz-Egea et al. with modifications regarding incubation time. The study included clarithromycin in the culture medium at a concentration achievable in the lungs (11.3 mg/L), using one row of wells as the control without antibiotics. The bacterial viability inside the biofilm is expressed as a percentage of viable cells. The differences between the different parameters of the biofilm ultrastructure were analyzed by using the Kruskal-Wallis test. The correlation between bacterial viability in the biofilm and treatment time was evaluated by using Spearman's rank correlation coefficient (ρ). Results: The strains showed differences between them with all the studied parameters, but neither a species-specific pattern nor a clinical-significance-specific pattern were detected. For the effect of clarithromycin, the viability of the bacteria contained in the biofilm was inversely proportional to the exposure time of the biofilm (ρ > −0.3; p-value < 0.05), excluding two M. chimaera strains (M. chimaera DSM756 and 575), which showed a weak positive correlation with treatment time (0.2 < ρ < 0.39; p-value < 0.05). Curiously, despite a clarithromycin treatment of 216 h, the percentage of the biofilm viability of the strains evaluated here was not less than 40% at best (M. avium 717). Conclusions: All the M. avium complex strains studied can form biofilm in vitro, but the ultrastructural characteristics between them suggest that these are strain-specific characteristics unrelated to the species or the clinical significance. The clarithromycin effect on MAC species is biofilm-age/time-of-treatment-dependent and appears to be strain-specific while being independent of the clinical significance of the strain.